Theory about traumatic brain injury effects. Part I. Definitions, classification, clinical signs and quantitative tomography - Leonid B. Likhterman; Aleksandr D. Kravchuk; Vladimir A. Okhlopkov (LLC "MEDIAFORMAT", 2021)
The paper presents the experience of assessment and treatment of 5000 cases of various traumatic brain injury (TBI) effects using brain imaging methods, minimally invasive and reconstructive neurosurgery. Definitions of TBI "effects" and "complications" have been proposed for the first time. Clinical and morphological classification of those has been developed, which identifies tissue effects, effects on cerebrospinal fluid system dynamics, and vascular effects of TBI. The major clinical symptoms of TBI effects have been described: neurologic deficit, mental dysfunctions, disturbances of vegetative function, epilepsy. Focal and diffuse alterations in brain tissue, intrathecal space and ventricular system resulting from TBI, identified by x-ray computed tomography, have been systematized. This has become the basis for investigation of pathogenesis and sanogenesis of brain disorders resulting from TBI, as well as for developing theory about the TBI effects.